Assessment of targets of antibody drug conjugates in SCLC - Abhishek Ajay; Han Wang; Ali Rezvani; Omid Savari; Brandon J. Grubb; Karen S. McColl; Suzy Yoon; Peronne L. Joseph; Shelby R. Kopp; Adam M. Kresak; Craig D. Peacock; Gary M. Wildey; et al. (npj Precision Oncology)
Abstract Antibody-drug conjugate (ADC) therapy has transformed treatment for several solid tumors, including small cell lung cancer (SCLC). However, significant challenges remain, including systemic toxicity, acquired resistance, and the lack of reliable biomarkers for patient selection. To enhance the effectiveness of ADC therapies in SCLC, we focused on target selection in this study by investigating the expression of ADC targets - SEZ6, DLL3, CD276, and TACSTD2 - in cell lines and patient samples. SEZ6 expression was significantly elevated in various SCLC transcriptional subtypes, particularly ASCL1, and exhibited gender-specific differences, being lower in women. DLL3 was primarily observed in the ASCL1 subtype, while CD276 showed high expression in non-neuroendocrine subtypes. TACSTD2 levels were generally low and attenuated in lymph nodes and brain metastases compared to primary tumors. Our findings underscore the importance of understanding target expression patterns to optimize ADC therapy and advance precision medicine in SCLC treatment.